Study on the Hydraulic Parameters of Woshaxi Landslide Soils during Water Level Drawdown of Three Gorges Reservoir. (13th January 2020) - Zhang, Zhenhua; Huang, Xiaoyu; Liu, Wu; Wang, Liang
Abstract : Variation of hydraulic parameters for unsaturated soil in bank slopes during reservoir water rising or falling process is crucial to scientific analysis and evaluation of bank slope stability. In this paper, soil samples from the Woshaxi landslide in the Three Gorges Reservoir were taken for a permeability test under reservoir drawdown conditions using an independently developed apparatus, which can simulate the variation process of internal seepage in bank slope soils. Changes of particle gradations, soil-water characteristic curves, and unsaturated permeability functions of the soil samples during reservoir falling process were studied by combining with the physical empirical model and numerical simulation. Permeability test results show that fine particles in soil samples migrated and were lost under seepage force action during the tests, leading to a continuous decrease of fine particle content indicated in the grain size distribution curves, in which particles with a size less than 0.02 mm lose the most. As permeation time increases, the soil saturated permeability enhances constantly with the change rate increasing first and then decreasing. The soil-water characteristic curves change obviously in the high matrix suction section (10 10 4 kPa), and the volumetric water content decreases constantly and shows a positive correlation with the fine particle content. During the permeability test, the unsaturated permeability coefficient corresponding to a fixed matric suction increases with the drawdowns of the reservoir water level. Slope stability results show that neglecting the variational characteristics of hydraulic parameters in slope stability evaluation can result in a bigger safety factor, which is dangerous for slope safety evaluation. The research results can provide a scientific basis for the stability analysis and evaluation of the bank slopes in the Three Gorges Reservoir Area.